Development of food packaging through triz and the possibility of open innovation - Harry Jeong; Seunggu Lee; Kwangsoo Shin (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
As the aging population increases, the need for new product development (NPD) for elderly-friendly food packaging is also increasing. Through the use of consumer research, this study derived the following problems when elderly people use food packaging: "The contents easily overflow when holding the container", "It is hard to pour", "Remnant remains after pouring", and "It is hard to use a straw". To address these problems, this study applied the following principles of TRIZ: principle 1 (segmentation) and principle 22 (blessing in disguise). In order to materialize the improvement plan, this study developed an elderly-friendly pouch-based packaging from the perspective of universal design. This study shows that it is possible to use the TRIZ technique in the NPD of food packaging, and that it is possible to secure commercial competitiveness from the view of universal design. This study is expected to serve as a starting point for further study on the NPD of elderly-friendly food packaging.
Keywords: 650; aged; aging; aging consumer; elderly friendly; open innovation; problem solving; senior friendly; silver food; TRIZ; universal design